(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: The vascular system is a vast network of vessels through which blood circulates in the body.Blood leaving the ventricles is distributed through arteries and arterioles in progressively smaller branchesto the capillaries Deep vein thrombosis is a medical condition that occurs when a blood clot forms in a deepvein. A world wide survey conducted by CDC shows that 900,000 people could be affected by DVT (1 to 2per 1,000) each year in the United States. Among people who have had a DVT, one-half will have long-termcomplications. DVT is a serious condition that can be life-threatening. However, it’s largely preventable andtreatable. Aim: To assess the knowledge and practice regarding prevention of deep vein thrombosis amongbedridden patients. Materials and Methods: A cross-sectional study was carried out among the bedriddenpatients of Yenepoya Medical College Hospital, Mangalore. The content validity of the tool was establishedin consultation with 7 experts. The reliability of the tools were found to be r (6) = 0.8 and 0.7 which wasstatistically significant. The tools were found to be reliable. Non probability convenience sampling was usedto select the subjects for the study. Pilot study was conducted to find out the feasibility of the study. Datacollected from the 95 subjects were analyzed by descriptive and inferential statistics using SPSS (Version23). Results: The findings of the study demonstrated that among 95 bedridden patients, that maximumpercentage (61%)were belonged to the age group of 47 years and above. Majority (72%) were males.(41%) of were completed primary education. Majority (62%) of the respondents were physically activeworkers.58% of subjects had inadequate knowledge and 42% of subjects had moderate knowledge and noneof the subjects had adequate knowledge on prevention of deep vein thrombosis and 22% of subjects had lowpractice, whereas majority 66% of respondents had moderate practice level and 12% of subjects had highpractice level. Mean knowledge score was 11.14 and mean practice score was 9.85. There existed a positiverelationship between knowledge and practice (correlation coefficient =0.662*) at 0.05 level of significance.The study also indicated that chi-square value of demographic variables have no significant association withknowledge scores and practice scores of bedridden patients.